Genetic variation in morphological traits in cotton and their roles in increasing phosphorus-use-efficiency in response to low phosphorus availability - Kayoumu, Mirezhatijiang; Li, Xiaotong; Iqbal, Asif; Wang, Xiangru; Gui, Huiping; Qi, Qian; Ruan, Sijia; Guo, Ruishi; Dong, Qiang; Zhang, Xiling; Song, Meizhen (Frontiers in Plant Science, 2022)
Phosphorus (P) is an essential macronutrient required for fundamental processes in plants. Trait plasticity is crucial for plant adaptation to environmental change. Variations in traits underlie diverse phosphorus (P) acquisition strategies among plants. Nevertheless, how the intraspecific plasticity and integration of morphological traits contribute to Phosphorus-Use-Efficiency (PUE) in cotton is unknown. In this study, 25 morphological traits were evaluated in 384 cotton genotypes grown with low P (LP, 10μmol. L−1) and normal nutrition (CK, 500μmol. L−1) to assess the genetic variability of morphological traits and their relationship to phosphorus use efficiency. Results revealed a large genetic variation in mostly morphological traits under low P. Significant enhancement in root traits and phosphorus efficiency-related traits like PUE was observed at LP as compared to CK conditions. In response to low P availability, cotton genotypes showed large plasticity in shoot and total dry biomass, phosphorus, and nitrogen efficiency-related traits (i.e., phosphorus/nitrogen use efficiency, phosphorus/nitrogen uptake efficiency), and most root traits, but a limited response in root dry biomass, taproot length, root surface area, root volume, and SPAD value. In addition, significant correlations were observed between PUtE (phosphorus uptake efficiency), NUE (nitrogen use efficiency), TDB (total dry biomass), and RTD (root tissue density) with PUE under both P supply level and phosphorus stress index, which may be a key indicator for improving PUE under LP conditions. Most root traits are most affected by genotypes than nutrition level. Conserved PUE is more affected by the nutrition level than the genotype effect. Principal component analysis depicted the comprehensive indicators under two P supply conditions were mainly reflected in root-related traits and morphological indicators such as dry matter biomass. These results indicate that interspecific variations exist within these cotton genotypes and traits. Our study provides suggestions for future research to enhance the ability of the earth system model to predict how crops respond to environmental interference and provide target quality for cotton breeding in phosphorus-deficient areas.